Intratumor Heterogeneity of MIF Expression Correlates With Extramedullary Involvement of Multiple Myeloma - Xu, Juan; Yu, Nanhui; Zhao, Pan; Wang, Fangfang; Huang, Jingcao; Cui, Yushan; Ding, Hong; Yang, Yan; Gao, Yuhan; Pan, Ling; Chang, Hong; Wu, Yu; et al. (Frontiers in Oncology, 2021)
Macrophage migration inhibitory factor (MIF) has been shown to promote disease progression in many malignancies, including multiple myeloma (MM). We previously reported that MIF regulates MM bone marrow homing and knockdown of MIF favors the extramedullary myeloma formation in mice. Here, based on MIF immunostaining of myeloma cells in paired intramedullary and extramedullary biopsies from 17 patients, we found lower MIF intensity in extramedullary MM (EMM) versus intramedullary MM (IMM). Flow cytometry and histology analysis in xenograft models showed a portion of inoculated human MM cells lost their MIF expression (MIFLow) in vivo. Of note, IMM had dominantly MIFHigh cells, while EMM showed a significantly increased ratio of MIFLow cells. Furthermore, we harvested the extramedullary human MM cells from a mouse and generated single-cell transcriptomic data. The developmental trajectories of MM cells from the MIFHigh to MIFLow state were indicated. The MIFHigh cells featured higher proliferation. The MIFLow ones were more quiescent and harbored abundant ribosomal protein genes. Our findings identified in vivo differential regulation of MIF expression in MM and suggested a potential pathogenic role of MIF in the extramedullary spread of disease.